Acute Necrotizing Encephalopathy of Childhood: A Case Report - Loni, Ramaning; Rajebhosale, Prashant; Bhateja, Priyanka; Konde, Santosh (Indian Journal of Child Health, 2020)
Acute necrotizing encephalopathy of childhood is uncommon, rare, and fatal encephalopathy, which usually occurs after respiratory or gastrointestinal infections. The disease was first described in Japan by Mizughuchi in the year 1995 (1). The characteristic clinical and magnetic resonance imaging brain findings were noticed in the index child following human herpes virus-6 viral infection. A number of metabolic encephalopathies and other para-infectious conditions have to be excluded to make the final diagnosis. It carries poor prognosis, but our child recovered well after early steroid therapy.